Alpha-Blocker Use and the Risk of Hypotension and Hypotension-Related Clinical Events in Women of Advanced Age. Issue 3 (September 2019) - Hiremath, Swapnil; Ruzicka, Marcel; Petrcich, William; McCallum, Megan K.; Hundemer, Gregory L.; Tanuseputro, Peter; Manuel, Douglas; Burns, Kevin; Edwards, Cedric; Bugeja, Ann; Magner, Peter; McCormick, Brendan; et al.
Abstract : Alpha-blockers (ABs) are commonly prescribed as part of a multidrug regimen in the management of hypertension. We set out to assess the risk of hypotension and related adverse events with AB use compared with other blood pressure (BP) lowering drugs using a population-based, retrospective cohort study of women (≥66 years) between 1995 and 2015 in Ontario, Canada. Cox proportional hazards examined the association of AB use and hypotension and related events (syncope, fall, and fracture) compared with other BP lowering drugs matched via a high dimensional propensity score. The primary outcome was a composite of hospitalizations for hypotension and related events (syncope, fractures, and falls) within 1 year. From 734 907 eligible women, 14 106 were dispensed an AB (mean age, 75.7; standard deviation 6.9 years, median follow-up 1 year) and matched to 14 106 dispensed other BP lowering agents. The crude incidence rate of hypotension and related events was 95.7 (95% CI [confidence interval], 90.4–101.1, events 1214 [8.6%]) with AB and 79.8 (95% CI, 74.9–84.7 per 1000 person-years, events 1025 [7.3%]) with other BP lowering medications (incident rate ratio, 1.20; 95% CI, 1.10–1.30). The risk was higher for hypotension (hazard ratio, 1.71; 95% CI, 1.33–2.20) and syncope (hazard ratio, 1.44; 95% CI, 1.18–1.75) with no difference in falls, fractures, adverse cardiac events, or all-cause mortality. Treatment of hypertension in women with ABs is associated with a higher risk of hypotension and hypotension-related events compared with other BP lowering agents. Our findings suggest that ABs should be used with caution, even as add on therapy for hypertension. Abstract : Supplemental Digital Content is available in the text.